Editorial 2.3 - Carroll, J. (Journal of University Teaching and Learning Practice, 2005)
The overarching theme for this special edition is academic integrity. The theme prompted papers which ranged widely in stance, purpose and methodology from authors in Australia and New Zealand. Many authors began by defining words (i.e. ’integrity’, ’plagiarism’ or ’original’) and I propose doing the same in these opening remarks. The word that struck me in the JUTLP title was ’practice’ and I kept that word in mind when selecting papers. I was asking myself: ’How might the special edition address the needs of practitioners themselves? What can the authors contribute to issues effecting teachers, students, university administrators and/or other researchers concerned with actions and interventions designed to encourage academic integrity? The result was accepting more papers than could be accommodated in a single issue. It may be that the volume of submissions just reflects academics’ need to publish but more positively, it could also indicate how much energy and thought is being expended by practitioners in universities on this issue. These papers all offer something useful, I believe, to one or more of the practitioner groups.